On Bivariate Distributions with \(N\) Deleted Areas: Mathematical Definition - El-Hadidy, Mohamed Abd Allah; Alraddadi, R. (Communications in Mathematics and Applications, 2024)
A new definition of deleting \(N\)-intervals from the domain of two random variables which have known bivariate distribution (\(N\)-truncated bivariate distribution) has been provided. This type of distribution is useful in real life applications, where it gives us the opportunity to delete \(N\)-intervals of data. This will increase the accuracy of statistical analysis, which facilitates decision-making. As a result of this multiple truncation, changes occur in the statistical properties of the bivariate distribution from its original version. We have thoroughly processed these properties and applied this definition to the bivariate normal distribution.
Keywords: Bivariate distribution; Statistical properties; N deleted areas; Moments